Entrepreneurship education 2-in-1: Helping young Bulgarians become more entrepreneurial in a 10-month parallel-group randomized trial - Daniel Vankov; Borislav Vankov (Journal of Innovation and Entrepreneurship, 2023)
Entrepreneurship education can help young people escape unemployment. It is often delivered through education programs or experiential learning. There is limited knowledge of the effect of those two approaches when applied as part of a single integrated innovative intervention. Our research aimed to address this gap in a parallel-group randomized trial. The Social Cognitive Theory underpinned our study method. The impact of our two-component program on 34 young participants aged 18 to 25, 16 intervention and 18 control, was assessed over a 10-month pilot. ANCOVA analyses were performed to examine separately for changes in the Intervention participants' entrepreneurial intention and self-efficacy (across six sub-dimensions) relative to the Control group. Our results showed a statistically significant impact on the male participants only. They were delivered by the experiential learning component of our intervention. Effects were observed on all measures except for two sub-dimensions, coping with unexpected challenges and developing critical human resources. Our article contributes to the discussions on entrepreneurship programs' effectiveness and the value of researching gender in that context, providing evidence in support of using experiential learning. It further underlines the importance of understanding the environment, where programs are delivered, particularly about external influences participants might be subjected to. At the same time, we acknowledge the challenges of generalizing our contribution due to our study being a trial with a limited number of participants. To further support our conclusions, we recommend replicating the study with larger samples and/or in different environments.
Keywords: 650; Entrepreneurial intention; Entrepreneurship education; Bulgaria; Entrepreneurial self-efficacy; Experiential learning; Social cognitive theory; Young people